Developing A Holistic Project Time Management Framework Utilizing Fundamental Supply Chain Management (SCM) Tools to Overcome Delay in Malaysian Public Sector Building Projects - Mehdi Riazi, Salman Riazi; Mohd Nawi, Mohd Nasrun; Abu Yaziz, Mohd Fathi (International Journal of Sustainable Construction Engineering and Technology, 2020)
Project delays have been an incessant dilemma worldwide and also for the Malaysian public sector projects. Past three Malaysia Plans (RMK8, RMK9, and RMK10) have experienced ridiculously high delay rates. Surprisingly, these poor delivery records have not led to much research on the topic locally especially those concerning past Malaysia Plans. Beyond that, despite â€œblame-gamesâ€ being a common picture when delay occur, past studies has been short of detecting their latent contributors to make delay easier to manage. Condemnations targeted on the industry have encouraged â€œcalls for changeâ€ and many proposed Supply Chain Management (SCM) as the way to go about. SCM has been proven to reduce delays nevertheless, level of applications are still very poor and past studies lacked holistic approach. This paper presents an on-going research aimed at developing a holistic project time management framework utilizing fundamental Supply Chain Management (SCM) tools to overcome delays in Malaysian public sector building projects. Data collections would include qualitative methods in form of expert opinion interviews and also a series of focus group sessions towards gathering vastly experienced industry practitioner to contribute towards the development of final research framework. The ultimate outcome is expected to provide a holistic guide on utilizing wide-range SCM tools towards mitigating various facets of delay contributors and with proven success from past SCM tool applications leads to a cautious optimism that it could benefit project time performances in Malaysia as a whole.